The policy of the ISO 9001 :2008 Quality Standard School - Asmoni, Asmoni; Bafadal, Ibrahim; Ulfatin, Nurul; Kusmintardjo, Kusmintardjo (Journal of Social Sciences (COES&RJ-JSS), 2017)
This research was aimed at finding out the implementation of the ISO9001:2008 of the State Vocational Senior High School 1 in Sumenep, Madura, East Java Indonesia in three different sites for three different departments. This research employed the qualitative approach using the multisites design. Data were collected using interview, documentation, and observation. The research found out that the implementation of the ISO9001:2008 in three different sites of the Vocational Senior Hogh School 1 in Sumenep, Madura, East Java was expereinced through integrative processes and steps to produce qualified outputs covering the planning and implementation of the site visit quality policy, the formulation of the policy of the quality, and the evaluation as well as monitoring of the implementation of the policy of the quality. The scope of the ISO standardization included 8 (eight) major business processes which included the so-called WMM, Vice of curriculum, Vice head master of students affair, Vice headmaster of school, Public Realtion and the so-called HKI/HUBINinfrastructure, Administration, Library. The results revelaed that the compliance reached in a range of 88% to 100%.